Effect of Angiotensin–Neprilysin Versus Renin–Angiotensin System Inhibition on Renal Outcomes: A Systematic Review and Meta-Analysis - Xu, Ying; Chen, Yang; Zhao, Jia Wei; Li, Chao; Wang, Amanda Y (Frontiers in Pharmacology, 2021)
Aims We aim to perform a systematic review and meta-analysis examining randomized controlled trials assessing the efficacy and safety of sacubitril/valsartan in patients on renal outcomes, in comparison with renin-angiotensin-aldosterone system inhibitor (RAASi). Methods Eligible studies were retrieved on MEDLINE, EMBASE and Cochrane till September 2021. The primary outcome was the incidence of renal impairment which was defined as a composite of increases in serum creatinine by >0.3mg/dl and/or a reduction in eGFR ≥25%, development of ESRD or renal death. We pooled relative risks (RRs) with 95% confidence intervals (CIs) or the weighted mean difference with 95% CIs for the variables. Results Our search yielded ten randomized controlled trials with a total of 18362 patients. Compared to RAASi treatment, patients treated with sacubitril/valsartan had lower incidence of composite renal impairment (10 studies, 18362 patients, RR 0.84; 95%CI 0.72-0.96, p=0.01; I2=22%), ESRD development (3 studies, 13609 patients, RR 0.53; 95%CI 0.30-0.96, p=0.03; I2=0%), drug discontinuation due to renal events (4 studies, 9995 patients, RR 0.58; 95%CI 0.40-0.83, p=0.003; I2=47%), severe hyperkalemia (6 studies, 16653 patients, RR 0.80; 95%CI 0.68-0.93, p=0.01; I2=25%) and a slower eGFR decline (4 studies, 13608 patients, WMD 0.56; 95%CI 0.36-0.76, p<0.00001; I2=65%). Subgroup analysis demonstrated sacubitril/valsartan was associated with a lower incidence of renal impairment in patients with heart failure and preserved ejection fraction (HFpEF), but not in those with heart failure and reduced ejection fraction (HFrEF). The superior renal function preservation of sacubitril/valsartan treatment was not associated with different baseline eGFR levels and follow-up duration. There was a smaller increase in the change of the Urine Albumin-to-Creatinine Ratio (UACR) (3 studies, 9114 patients, SMD 0.06; 95%CI 0.02-0.10, p=0.003; I2=14%) with sacubitril/valsartan treatment. However, patients with HF appeared to have increased microalbuminuria, not patients without HF (p=0.80 for interaction). Conclusions Sacubitril/valsartan was associated with a lower incidence of composite renal impairment especially in patients with HFpEF, but higher microalbuminuria in patients with HF (both HFrEF and HFpEF) compared to RAASi. The lower incidence of severe hyperkalemia and drug discontinuation due to renal events in patients with sacubitril/valsartan treatment demonstrated its superior safety compared to RAASi.